2020
DOI: 10.1111/jcpt.13294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proprotein convertase subtilisin/kexin type 9 and nilotinib plasma concentrations on nilotinib‐induced hypercholesterolaemia in patients with chronic myeloid leukaemia

Abstract: What is known and objective The purpose of this study was to investigate the relationships among nilotinib plasma trough concentration (C0), low‐density lipoprotein (LDL) cholesterol, and PCSK9 plasma concentration in 31 patients with chronic myeloid leukaemia. Methods Plasma concentrations of nilotinib and PCSK9 were measured by high‐performance liquid chromatography and enzyme‐linked immunosorbent assays, respectively. Results and discussion LDL cholesterol concentrations at 1 month after nilotinib treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…These changes happen early at the beginning of treatment-within the first 12 monthsand are kept during treatment. [34][35][36] Regarding TOD, 8.20% of our patients had LVH while 19.20% had microalbuminuria. A total of 26% of these patients had elevated PWV levels while 32.90% had elevated US-CRP levels.…”
Section: Discussionmentioning
confidence: 69%
“…These changes happen early at the beginning of treatment-within the first 12 monthsand are kept during treatment. [34][35][36] Regarding TOD, 8.20% of our patients had LVH while 19.20% had microalbuminuria. A total of 26% of these patients had elevated PWV levels while 32.90% had elevated US-CRP levels.…”
Section: Discussionmentioning
confidence: 69%
“…Nilotinib produces an early increase in the LDL levels, since the first month of the treatment, secondary to the higher concentration of proprotein convertase subtilisin/kexin type 9 (PCSK9), due to the mTORC1 inhibition, among other causes 14 . Besides, it has been observed that these patients present higher concentrations of LDL oxidatively modified (oxLDL) than the patients treated with imatinib and dasatinib, as demonstrated by the KIARO study in a recently published multicenter study 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Se ha especulado con que el nilotinib podría, en algunos casos, aumentar las cifras de colesterol vinculado a lipoproteínas de baja densidad (c-LDL) de forma secundaria al incremento en la concentración de la proproteína convertasa subtilisina/kexina tipo 9 (PCSK9), mediado por la inhibición de mTORC1. Estos cambios se producen de forma precoz al inicio del tratamiento, en los primeros 12 meses, y se mantienen durante el tratamiento [34][35][36] .…”
Section: Discussionunclassified